Effects of exercise on physical outcomes of breast cancer survivors receiving hormone therapy – A systematic review and meta-analysis - Boing L.* (2020)
© 2020 Elsevier B.V.Background: Side-effects of hormone therapy can impair the physical health of breast cancer survivors. Exercise has been clearly shown to improve the quality of life of breast cancer survivors. Less is known about the effects of exercise on physical outcomes for breast cancer survivors receiving hormone therapy. Objective: To investigate the effects of exercise on physical outcomes of breast cancer survivors receiving hormone therapy. Methods: Five electronic databases were searched by two authors using the terms “Breast Neoplasms” [MeSH] and “Tamoxifen” [MeSH] and “Aromatase Inhibitors” [MeSH] and “Exercise” [MeSH]. Randomized and non-randomized clinical trials were included. Risk of bias was assessed by the Cochrane Collaboration tool and ROBINS-I, and the quality of evidence was evaluated using GRADE. Pooled effects were reported as standardized mean differences (SMDs) and 95 % confidence intervals (CIs) using a random effects model. Results: Eleven studies were included in the meta-analysis. Two hundred and fourteen breast cancer survivors receiving hormone therapy, tamoxifen, or aromatase inhibitors participated in interventions based on aerobic plus resistance exercise or walking activity. The physical outcomes reported in the articles were: cardiorespiratory fitness, pain, bone mineral density, grip strength, and body fat percentage. Exercise effects were found only for cardiorespiratory fitness (SMD = 0.37; 95 % CI: 0.11; 0.63; I2 = 93 %) and pain (SMD = −0.55; IC95 % −1.11; −0.00; I2 = 80 %), with low quality of evidence. No effects were observed for the other variables. Conclusions: Aerobic plus resistance exercise had positive effects on cardiorespiratory fitness and pain in breast cancer survivors receiving hormone therapy. However, high-quality randomized clinical trials are required to confirm this finding.